2018
DOI: 10.1111/hel.12494
|View full text |Cite
|
Sign up to set email alerts
|

Retrospective study on outcome of salvage Helicobacter pylori eradication therapies based on molecular genetic susceptibility testing

Abstract: Eradication success was poor despite susceptibility testing. Gastroenterologists are advised to prescribe recommended salvage treatments, considering recommended dosages and prolonged treatment duration.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
22
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(22 citation statements)
references
References 28 publications
0
22
0
Order By: Relevance
“…Drug resistance among clinical isolates of H. pylori is a well-recognized issue, and susceptibility-guided treatment of H. pylori infection is crucial to attain a better treatment response among infected individuals (41). WHO has listed H. pylori as a highpriority pathogen for which there is an urgent need to develop new antimicrobials (42).…”
Section: Discussionmentioning
confidence: 99%
“…Drug resistance among clinical isolates of H. pylori is a well-recognized issue, and susceptibility-guided treatment of H. pylori infection is crucial to attain a better treatment response among infected individuals (41). WHO has listed H. pylori as a highpriority pathogen for which there is an urgent need to develop new antimicrobials (42).…”
Section: Discussionmentioning
confidence: 99%
“…The limitations of this study are the lack of a reference method for clarithromycin resistance, the lack of samples of non-infected individuals to determine the specificity of the method for the detection of infection when using FFPE tissue, and the lack of information on previous eradication therapies. 34 In this context, two similar studies from Korea showed significantly higher eradication rates of tailored firstline therapies in comparison with the conventional empirical triple therapy consisting of clarithromycin, amoxicillin and a PPI. The latter showed the highest positivity rate, which was not affected by the use of PPI in contrast to the other methods.…”
Section: Molecular Methodsmentioning
confidence: 97%
“…Even though current guidelines recommend susceptibility testing to be performed only after two treatment failures, the authors conclude that it may be reasonable to perform susceptibility testing as early as possible, since tailored first-line treatments are superior to empiric ones and may also be cost-effective. 34 In this context, two similar studies from Korea showed significantly higher eradication rates of tailored firstline therapies in comparison with the conventional empirical triple therapy consisting of clarithromycin, amoxicillin and a PPI. In both studies, tailored treatment was guided by molecular detection of mutations associated with clarithromycin resistance in gastric biopsies; however, there was some controversy regarding the costeffectiveness of this approach which depends on local costs.…”
Section: Molecular Methodsmentioning
confidence: 97%
“…33 Cure, however, was only achieved in 68% of patients. A German study looked at real-time genotypic clarithromycin and/or levofloxacin susceptibility as tested by PCR analysis of 144 H pylori-positive strains from patients with prior treatment failure.…”
Section: Suscep Tib Ilit Y-g Uided Ther Apymentioning
confidence: 93%
“…A German study looked at real-time genotypic clarithromycin and/or levofloxacin susceptibility as tested by PCR analysis of 144 H pylori-positive strains from patients with prior treatment failure. 33 Cure, however, was only achieved in 68% of patients. More encouraging results were obtained in a large, multicenter open-label trial of 450 patients who had failed two previous treatment regimes where genotypic resistance tailored treatment led to 78% eradication, but in this case empirical quadruple sequential therapy with a cure rate of 71% was an acceptable alternative after consideration of accessibility, cost, and patient preference.…”
Section: Suscep Tib Ilit Y-g Uided Ther Apymentioning
confidence: 93%